Generic windowing support for extensible stream processing systems. (26th March 2013) - Gedik, Buğra
SUMMARY Stream processing applications process high volume, continuous feeds from live data sources, employ data‐in‐motion analytics to analyze these feeds, and produce near real‐time insights with low latency. One of the fundamental characteristics of such applications is the on‐the‐fly nature of the computation, which does not require access to disk resident data. Stream processing applications store the most recent history of streams in memory and use it to perform the necessary modeling and analysis tasks. This recent history is often managed using windows. All data stream management systems provide some form of windowing functionality. Windowing makes it possible to implement streaming versions of the traditionally blocking relational operators, such as streaming aggregations, joins, and sorts, as well as any other analytic operator that requires keeping the most recent tuples as state, such as time series analysis operators and signal processing operators. In this paper, we provide a categorization of different window types and policies employed in stream processing applications and give detailed operational semantics for various window configurations. We describe an extensibility mechanism that makes it possible to integrate windowing support into user‐defined operators, enabling consistent syntax and semantics across system‐provided and third‐party toolkits of streaming operators. We describe the design and implementation of a runtime windowing library that significantly simplifies the construction of window‐based operators by decoupling the handling of window policies and operator logic from each other. We present our experience using the windowing library to implement a relational operators toolkit and compare the efficacy of the solution to an earlier implementation that did not employ a common windowing library. Copyright © 2013 John Wiley & Sons, Ltd.